'It's more foreign than a foreign country': adaptation and experience of Mainland Chinese students in Hong Kong. Issue 4 (1st October 2016) - Yu, Baohua; Zhang, Kun
Abstract : Recent years have witnessed an increasing number of Mainland students crossing the border to pursue tertiary studies in Hong Kong, a Special Administrative Region of the People's Republic of China. In contrast to those who have chosen to study in foreign countries, such as United States, United Kingdom or Germany, the Mainland group are studying and living in a society that is both familiar and strange to them due to unique political and sociocultural relationships between Hong Kong and the Mainland. Previous research has mainly focused on Mainland students' motivations for choosing Hong Kong as their academic destination, but questions as to how they adapt to the university setting and host society have been under-researched. Adopting a qualitative approach, this study reports on the findings of focus groups exploring Mainland students' adaptation to life and study in Hong Kong. Findings revealed that linguistic adaptation, social network, political identification and discrimination were the most significant acculturative stressors reported by Mainland students. Implications for how Mainland students can best adjust and how universities can better support them are discussed.